2008
DOI: 10.1080/14622200701825023
|View full text |Cite
|
Sign up to set email alerts
|

Waterpipe tobacco smoking: Knowledge, attitudes, beliefs, and behavior in two U.S. samples

Abstract: Despite evidence of increasing waterpipe tobacco smoking prevalence among U.S. young adults, little is known about the knowledge, attitudes, beliefs, and smoking patterns of waterpipe users in this population. To address this lack of knowledge, two convenience samples of U.S. waterpipe users were surveyed-one from a Richmond, Virginia, waterpipe café (n=101), the other from an Internet forum called HookahForum.com (n=100). Sixty percent reported first-time waterpipe use at or before age 18. Daily waterpipe use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

26
298
2
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 303 publications
(333 citation statements)
references
References 19 publications
26
298
2
7
Order By: Relevance
“…It is clearly evident from Table 4 that majority (71-80%) of the participants in the present study consider hookah smoking to be less dangerous and less harmful compared to cigarette smoking and this consideration is similar to the perception of the hookah smokers globally (Smith-Simone et al, 2008;Aljarrah et al, 2009;Combrink et al, 2010;Dar-Odeh et al, 2010;Jordon and Delenovo, 2010;AL-Naggar and Saghir Fatma, 2011). It appears to be a global phenomenon among the hookah smokers to have a false perception that hookah smoke is filtered through water and thus is less harmful in nature as compared to cigarette smoking (Aljarrah et al, 2009).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…It is clearly evident from Table 4 that majority (71-80%) of the participants in the present study consider hookah smoking to be less dangerous and less harmful compared to cigarette smoking and this consideration is similar to the perception of the hookah smokers globally (Smith-Simone et al, 2008;Aljarrah et al, 2009;Combrink et al, 2010;Dar-Odeh et al, 2010;Jordon and Delenovo, 2010;AL-Naggar and Saghir Fatma, 2011). It appears to be a global phenomenon among the hookah smokers to have a false perception that hookah smoke is filtered through water and thus is less harmful in nature as compared to cigarette smoking (Aljarrah et al, 2009).…”
Section: Discussionsupporting
confidence: 78%
“…In the present time, this ancient trend has re-emerged again. Different epidemiological studies related to hookah smoking have been conducted, which evaluate the attitudes, perceptions and behaviour of the youth and university students (Maziak, 2004;Smith-Simone et al, 2008;Aljarrah et al, 2009;Dar-Odeh et al, 2010;Jordan and Delnevo, 2010;Poyrazoglu et al, 2010;Ahmed et al, 2011;AL-Naggar and Saghir Fatma, 2011;Martinasek, 2011;Braun et al, 2012;Brockman et al, 2012;Nuzzo et al, 2012). No study was found, which relates to information about the personal characteristics, perceptions and behaviour of the hookah smokers in India.…”
Section: Introductionmentioning
confidence: 99%
“…Various fruit flavors seem to mask the toxic substances in the tobacco and this makes it less irritating, thus motivating them further to smoke (Marziak et al, 2004;Knishkowy and Amitai, 2005;Smith-Simone et al, 2008). Given that previous studies show most of the shisha users started with friends in café restaurants (Ward et al, 2007;Smith-Simone et al, 2008) and since this has mostly become a group socializing activity, we believe that those who are nonsmokers would eventually try shisha smoking and become users along with their friends. Several studies have shown that shisha smokers were significantly more likely to have shisha smokers as friends (Maziak et al, 2004, Mohammed et al, 2006.…”
Section: Discussionmentioning
confidence: 92%
“…80% was male and the mean age was 23 years. 40% of the smokers claimed that they do not smoke (Subasi et al, 2005;Smith-Simone et al, 2008 though narghile smoking likely exposes users to high levels of various toxicants and that the practice may be addictive , it is popularly perceived as less harmful and toxic than cigarette smoking because of the purported filtering effect of the water bubbler (Kandela, 2000;Ward et al, 2007;Smith-Simone et al, 2008;Griffiths et al, 2011;Al-Naggar and Bobryshev, 2012).Volatile aldehydes, especially formaldehyde, acetaldehyde and acrolein were shown in narghile smoke (Al Rashidi et al, 2008). These are associated with a significant number of cigarette smoking diseases including chronic pulmonary disorder and cancer (Cogliano et al, 2004).…”
Section: Introductionmentioning
confidence: 99%